Recent Studies on the Properties of Pervious Concrete; A Sustainable Solution for Pavements and Water Treatment - Vijavalakshmi, Ramalingam (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Pervious concrete a sustainable solution with limited fines or no fines and interconnected voids, has many environmental benefits, such as reducing the stormwater run-off, improving the groundwater table, reducing water pollution, and mitigating urban heat island. Many research works have been done in Pervious Concrete (PC) by varying different parameters such as, types of aggregate, aggregate gradation, water-to-cement (w/c) ratio, cement-to-aggregate ratio, geopolymer binder, ultra-high strength Matrix and compaction techniques.
Keywords: pervious concrete; permeability; porosity; pavements; purification; clogging; mitigating urban heat; beton porowaty; przepuszczalność; porowatość; chodniki; oczyszczanie; kolmatacja; łagodzenie miejskiego ciepła